Performance of active electrical earthing systems: results and discussion - Hamzah, M. N.; Gomes, C.; Afiq, M.; Ab Kadir, M. Z. A. (IEEE, 2023)
This paper presents the results of a long-term experiment on an active earth resistance reduction technique that can be used to increase the performance of electrical earthing systems. The technique employs an earth resistance reduction agent (ERRA) based on naturally occurring bentonite and an aluminium sacrificial electrode. The results show that not only the ERRA used but the sacrificial electrode configuration too will be of importance in achieving the desired performance of the grounding system.